Self-efficacy and the Related Factors in Ostomates - F Rafii; L Naseh; S Parvizy; H Haghani (Iran University of Medical Sciences, 2011)
Background & Aims: Stoma surgery is one of the events that strongly influences individual life and causes major changes in life style . Self-efficacy as a personal coping resource can facilitate adaptation with these changes . So the aim of this study was to assess self-efficacy and the related factors in ostomates.   Material & Methods: It was a cross-sectional study. Eighty four patients with ostomy who were referred to selected educational centers of Tehran University of Medical Sciences and Iranian Ostomy Association (IOA) were selected through convenience sampling. The data were collected using personal information form and Stoma Self-Efficacy Scale (Stoma SE Scale). Data was analyzed by SPSS 15 using descriptive statistics, independent t-test, ANOVA and regression analysis .   Results: Half of the participants gained at least half of the overall self-efficacy scores. The mean score of social self-efficacy was lower than the mean score of stoma care self-efficacy. Self-efficacy was associated with marital status, stoma status and stoma duration (P<0.05) but the relationship between self-efficacy and age, gender, educational level, type of stoma and reason of stoma was not statistically significant.   Conclusion: the Present study provided useful information about self-efficacy and its related factors in stoma patients. This information can be used for designing and performing appropriate nursing interventions to promote these patients' self-efficacy, especially in the social dimension which is weaker in most ostomates.